DEVELOPMENT AN AGGREGATE PLANNING MODEL FOR DISCRETE COMPONENT MANUFACTURING: A CASE STUDY FOR DISC BRAKE - Nur’Aisyah bt Marzuki, Nur’Aisyah (Universiti Teknologi Petronas, 2012)
This project develops the aggregate planning strategy model for manufacturing of the discrete component by using the spreadsheet excel and linear programming. Forecasting is function to create the future demand. In the case study project, the average forecasting method is applied to forecast the total demand. The models use the forecast demand for analysis the project. The data being use in the forecasting is taken from Malaysia Automotive Association website. The aggregate planning strategies that apply to evaluate the models are the constant workforce and production level strategy. The total number of workers was calculated and estimated using the demand and the cycle time. In this project, the author creates production planning that involve with casting process and machining process. Disc brakes production is used as the case study of this project. The aggregate planning consists of 2 types of models which are model A and model B. For model A, the casting process is subcontracting to third party while machining process is done in house. For model B, both processes are operated in house. The result of each strategy for model A and model B are included